2022
DOI: 10.1177/00469580221112832
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Perceived Access to Healthcare and the Perception of Illness Among Peruvian Adults with Chronic Diseases During COVID-19 Pandemic

Abstract: The COVID-19 pandemic has greatly affected the provision of care for patients with chronic diseases. Due to social restrictions and reductions in contact with health services, the negative perception of chronic disease is expected to have increased. The aim of this study was to determine the association between perceived access to healthcare and the perception of illness among Peruvian population with chronic disease. It was a cross-sectional analytical study, with a sample of 987 inhabitants to whom the quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“… 29 Furthermore, a study that assessed access to healthcare in a Peruvian population indicated that prolonged waiting times to obtain a medical appointment and limited access to healthcare were major factors influencing perceptions of chronic diseases, especially during the COVID-19 pandemic. 30 …”
Section: Discussionmentioning
confidence: 99%
“… 29 Furthermore, a study that assessed access to healthcare in a Peruvian population indicated that prolonged waiting times to obtain a medical appointment and limited access to healthcare were major factors influencing perceptions of chronic diseases, especially during the COVID-19 pandemic. 30 …”
Section: Discussionmentioning
confidence: 99%
“…These deficiencies in access have influenced how Peruvians perceive their government’s ability to provide adequate healthcare availability. A 2022 survey found that approximately 70% of Peruvian adults viewed their access to healthcare as deficient ( 49 ).…”
Section: Peru’s Healthcare System and Health Barriersmentioning
confidence: 99%
“… 2 , 9 , 10 , 17 , 18 , 19 , 20 , 21 Leventhal’s common-sense model of self-regulation is a comprehensive framework that has often been used to understand the self-management of chronic illnesses such as diabetes and inflammatory bowel disease, 22 , 23 but is rarely used in CKD. 24 , 25 , 26 This model highlights the role of cognitive beliefs, emotional reactions, and social-cultural influences in coping with health threats. 22 , 23 In the context of the COVID-19 pandemic, this model can elucidate how patients with CKD and their care partners perceive and respond to the risks and impact of COVID-19 on their kidney health and its potential implications for self-management behavior.…”
Section: Introductionmentioning
confidence: 99%